Isolation and characterization of piperine from the fruits of black pepper (Piper nigrum) - Saha, KC; Seal, HP; Noor, MA (Journal of the Bangladesh Agricultural University, 2014)
Black pepper (Piper nigrum) is a spice vine crop which is used as a food preservative and as an essential component in traditional medicines. The aim of this study was to extract, isolate and characterize the structure of piperine. The fruits of black pepper were extracted in ethanol and compounds present identified by TLC under iodine vapour. A compound (A2) having Rf value 0.54 was isolated by column chromatography which may be responsible for the pungency of black pepper. After recrystallization of the isolate with benzene and chloroform mixture (7:1) gave pale yellow crystals of m.p. 128~129oC (reported 130oC). The IR, 1H NMR and mass spectra of the pure crystalline compound (A2) were recorded. The mass spectra of the compound (A2) showed molecular ion peak M+· at 284.5 which was similar to that of piperine (mol. wt. 285). DOI: http://dx.doi.org/10.3329/jbau.v11i1.18197 J. Bangladesh Agril. Univ. 11(1): 11-16, 2013